Interest rate uncertainty as a policy tool - Fabio Ghironi; G. Kemal Ozhan (Bank of Canada, 2020)
We study a novel policy tool-interest rate uncertainty-that can be used to discourage inefficient capital inflows and to adjust the composition of external account between shortterm securities and foreign direct investment (FDI). We identify the trade-offs faced in navigating between external balance and price stability. The interest rate uncertainty policy discourages short-term inflows mainly through portfolio risk and precautionary saving channels. A markup channel generates net FDI inflows under imperfect exchange rate passthrough. We further investigate new channels under different assumptions about the irreversibility of FDI, the currency of export invoicing, risk aversion of outside agents, and effective lower bound in the rest of the world. Under every scenario, uncertainty policy is inflationary.
Keywords: E32; F21; F32; F38; G15; 330; International financial markets; Uncertainty and monetary policy; Monetary policy framework